Assessment of Basic Basketball Skills among Students Participating in a High School Basketball Extracurricular Program - Agung Nofri Syamwardana; Masrun; Muhammad Fakhrur Rozi; Eko Purnomo (STKIP Pasundan, 2026)
This study aimed to determine the level of basic basketball skills among students participating in the basketball extracurricular program at SMA Negeri 7 Padang. This research employed a quantitative descriptive design using a survey method. The population consisted of 20 male students participating in the basketball extracurricular program, and all participants were selected as the sample using the total sampling technique. Data were collected using the AAHPERD Basketball Test, which measures dribbling, shooting, and passing skills. The data were analyzed using descriptive statistics. The results showed that the average dribbling score was 21.71 seconds, the average shooting score was 32, the average passing score was 70, and the overall basic basketball skill T-score averaged 50. Overall, the participants' basic basketball skills were classified as moderate (fair). These findings indicate the need for more structured training programs and adequate sports facilities to improve students' basketball skills.